UNITED ARAB EMIRATES’ INTERESTS ON NET ZERO 2050 INITIATIVE - Lintang, Fauzan Akbar; Ramadhan, Iqbal Arya; Lathifa, Marianna Nur; Satria, Randhi (Jurnal Pena Wimaya, 2024)
The United Arab Emirates (UAE) has boldly embarked on an ambitious UAE Net Zero 2050 initiative aligned with their plan to integrate the vision of economic development with environmental sustainability. This strategic move signals a pivotal shift in the UAE's approach to balancing its role as a major oil producer with its commitment to global climate action. The initiative not only aligns with international climate goals but also caters to domestic sustainability interests, encapsulating the two-level game theory dynamic. UAE in their effort to secure its position as a leader in climate-responsive policy on the international stage while fostering green technology and renewable energy sectors domestically. The UAE's strategy involves negotiating these interests against the backdrop of domestic economic diversification goals and international pressure to reduce carbon emissions. The paper will analyze how the UAE navigates these complex layers of environmental diplomacy and policy-making, contributing to a deeper understanding of state behavior in the international climate change discourse.